STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT (LEGENDA SETEMPAT) PINCURAN TUJUAH DI KANAGARIAN SIKUCUA TIMUR KECAMATAN V KOTO KAMPUANG DALAM KABUPATEN PADANG PARIAMAN - Putra AF, Marzon; Nurizzati, Nurizzati (Jurnal Bahasa dan Sastra, 2018)
This study aims to describe: (1) folklore structure of local legend Tujuah in Kanagarian Sikucua Timur sub-district V Koto Kampuang Dalam Padang Pariaman district, (2) social function folklore local legend Tujuah in Kanagarian Sikucua Timur sub-district V district Koto Kampuang sub-district Padang Pariaman. This type of research is qualitative research using descriptive methods. The data of this research are folklore of local legends of Tujuah in Kanagarian Sikucua Timur, Subdistrict V, Koto Kampuang Dalam, Padang Pariaman District. The data in this study were analyzed in four stages, namely: (1) the data identification stage, the data collected from the informants were identified through two stages, namely: (a) the stage of transcription, transliteration, and (b) the stage of describing the results of observation, recording, and interview, (2) Data classification or analysis stage, (3) Discussion phase and conclusion of the results of classification or data analysis, (4) Reporting phase. Based on the results of the study, it can be concluded that the folklore structure of local legend Tujuah in Kanagarian Sikucua Timur, V Subdistrict, Koto Kampuang Dalam, Padang Pariaman Regency consists of, namely: (1) language style, language style speech used by folklore in local legend Folklore Pariaman dialect, (2) point of view, (3) character and character, figures found in local folklore local legend Pujuran Tujuah is divided into two, Sutan Bagindo as the main character, and Putri Bungsu, Mandeh Rubiah, Rajo Simanta as a side character, ( 4) background, background of folklore local legend Pujuran Tujuah is a setting, time setting and social setting, (5) plot / plot, plot / plot in folklore local legend Pincuran Tujuah is a conventional plot, and has three stages: , the initial stage or introduction (beginning), middle stage or conflict (midle), and the final stage or end (end), (6) themes, and (7) mandate. The social function of folklore local legend of the Tujuah Swamp in Kanagarian Sikucua Timur, V Koto Kampuang Dalam District, Padang Pariaman Regency, namely: (1) educating, and (2) entertaining.Keywords: folklore, legend, minangkabau